Does the severity of obesity influence bone density, geometry and strength in adolescents?. Issue 12 (25th June 2021) - Julian, Valérie; O'Malley, Grace; Metz, Lore; Weghuber, Daniel; Courteix, Daniel; Fillon, Alicia; Boirie, Yves; Duclos, Martine; Pereira, Bruno; Thivel, David
Summary: Background: Relationships between the severity of obesity and bone health remain underexplored. Objectives: To compare whole‐body and localized bone mineral content (BMC) and density (BMD), trabecular bone score (TBS) and hip geometry and strength between adolescents with obesity versus extreme obesity. Methods: This cross‐sectional study included 154 adolescents (12–15 years, 62% females) who were classified as having obesity (OG, [95th–99th] percentile) or extreme obesity (EOG, >99th percentile). Fat mass (FM), lean mass (LM), BMC, BMD for total‐body‐less‐head (TBLH), lumbar spine (LS), hip, TBS and geometric and strength indices at the narrow‐neck (NN), femoral shaft (FS) and intertrochanteric regions (IT) were assessed by Dual‐X‐ray Absorptiometry (DXA). Results: There was no significant sex‐interaction. For both sexes, TBLH BMC and BMD were not different between groups. TBS was lower in EOG compared with OG in both sexes in univariate analysis and after adjustment with maturation and body weight ( p < 0.05). Hip BMD was significantly higher in the EOG compared to OG only after adjustment with maturation and fat mass percentage ( p < 0.05 for men, p < 0.01 for women). For both sexes, TBLH, LS and hip BMC and BMD positively correlated with weight, BMI, LM and FM. TBS negatively correlated with BMI‐percentile in both sexes, with a negative correlation with FM for males alone. Hip BMC and BMD, BMD, ACT and CSA at the three hip sites positively correlated with BMI‐percentile in males. Conclusions: Extreme obesity impacts bone health depending on anatomical sites, altering lumbar trabecular bone in both males and females adolescents.